New Landscape, New Challenges : Structural Change and Regulation in the U.S. Financial Sector - Bhatia, Ashok (Washington, D.C. : International Monetary Fund, 2007)
Given the rapid evolution of the U.S. financial sector and attendant regulatory challenges, this paper explores ways to fine-tune U.S. oversight arrangements. It surveys the financial landscape, separating a highly regulated, multi-business, and (in terms of relative asset holdings) shrinking 'core' from a lightly regulated, more specialized, and rapidly expanding 'periphery' explains the U.S. regulatory philosophy and structure, with its focus on core institutions and its jurisdictional complexity; highlights certain new challenges, without presuming to have all the solutions; draws out some broad policy implications, from the '30,000 foot level' and concludes by tabling and discussing one, specific, reform idea.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet